2016
DOI: 10.1016/j.jstrokecerebrovasdis.2016.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Increased Blood Viscosity in Ischemic Stroke Patients with Small Artery Occlusion Measured by an Electromagnetic Spinning Sphere Viscometer

Abstract: Cover titleIncreased blood viscosity in patients with small artery occlusion Key wordsblood viscosity, ischemic stroke, small artery occlusion, pathogenesis, rheology, dehydration 2 Abstract Background and Purpose: High blood viscosity causes blood stagnation and subsequent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 30 publications
1
57
0
1
Order By: Relevance
“…2,3,5 Several studies have demonstrated associations between BV and ischemic stroke. 1,2,6 BV measurements are reportedly higher in lacunar stroke than in other stroke subtypes. Increased BV may impair microvascular tissue perfusion and be related to the pathomechanisms in lacunar stroke.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…2,3,5 Several studies have demonstrated associations between BV and ischemic stroke. 1,2,6 BV measurements are reportedly higher in lacunar stroke than in other stroke subtypes. Increased BV may impair microvascular tissue perfusion and be related to the pathomechanisms in lacunar stroke.…”
Section: Introductionmentioning
confidence: 84%
“…17 Recent studies, however, suggest that BV is significantly higher in lacunar stroke. 1,2 BV is dependent upon the aggregation of RBCs in small vessels at a low shear rate, equivalent to DBV. 18 Since DBV has a greater impact on the tissue perfusion of small vessels than SBV, DBV can be more likely to influence cerebral SVD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ESR value obtained from this comparison showed that the mean value of EDTA anticoagulated blood (57.90 mm/h) was greater than that of TSC blood (50.99 mm/h) by 6.91 mm/h. This may be because EDTA increases rouleaux formation more than TSC, leading to increases in ESR in EDTA blood, or it might be due to a difference in viscosity, where citrated blood may be less viscous than EDTA blood resulting in lower ESR values [34][35][36]. This observation corresponds to the result reported from Tehran University, Iran, and stated that there was a significant difference between the results of ESR tests which used two anticoagulants [37].…”
Section: Discussionmentioning
confidence: 99%
“…Actually, plasma fibrinogen played a major determinant in platelet aggregation and blood viscosity, whereas high blood viscosity led to blood stagnation and then promoted thrombosis, resulting in the development of ischemic stroke. [54,55] So evaluating the effect of puerarin injection on blood rheology indexes and fibrinogen was important. Moreover, our enrolled sample size was much larger and we focused on acute ischemic stroke treatment, whereas they included acute and chronic ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%